Work and Masculinity in Katanga’s Artisanal Mines - Jeroen Cuvelier (Africa Spectrum, 2014)
This article, based on 16 months of anthropological fieldwork between 2005 and 2012, examines the relationship between work and masculinity among artisanal miners, or creuseurs, in Katanga, the southeastern province of the Democratic Republic of the Congo. It argues that men’s involvement in artisanal mining should be considered not only as an economic survival strategy but also as an attempt to experiment with new ways of being a man in a context of economic crisis and changing gender relations. Furthermore, the article criticizes the tendency to downplay or underestimate the complexity and diversity of processes of masculine identity construction in Africa’s artisanal-mining areas. In order to do justice to the intricacy of these processes, the article proposes using concepts and insights from the field of masculinity studies and distinguishing between a levelling and a differentiating trend in artisanal miners’ masculinity practices.